2021
DOI: 10.1249/mss.0000000000002607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Exercise Strategies to Improve Postprandial Glycemia in Healthy Individuals

Abstract: PurposeWe systematically investigated the effects of different exercise strategies on postprandial glycemia.MethodsSix randomized repeated-measures crossover studies were performed. Study 1 compared the effects of 60 min of brisk walking started at 30, 60, or 90 min after breakfast on postbreakfast and postlunch glycemic responses. Study 2 investigated the effects of 30 min of different exercise types (aerobic vs resistance vs combined). Study 3 compared the effects of 30 min of different aerobic exercise type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(57 citation statements)
references
References 42 publications
4
53
0
Order By: Relevance
“…An accumulating body of evidence now suggests that postprandial glucose (PPG) is more closely correlated with microvascular and macrovascular morbidities and cardiovascular mortality than hemoglobin A1c (HbA1c) or fasting glucose [ 3 5 ]. The role of exercise in reducing PPG levels [ 6 , 7 ] and improving glycemic control and overall health [ 8 10 ] in diabetic, as well as in healthy, populations has been well established [ 11 , 12 ]. However, how and when aerobic exercise should be prescribed to optimize glucose control remains controversial [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…An accumulating body of evidence now suggests that postprandial glucose (PPG) is more closely correlated with microvascular and macrovascular morbidities and cardiovascular mortality than hemoglobin A1c (HbA1c) or fasting glucose [ 3 5 ]. The role of exercise in reducing PPG levels [ 6 , 7 ] and improving glycemic control and overall health [ 8 10 ] in diabetic, as well as in healthy, populations has been well established [ 11 , 12 ]. However, how and when aerobic exercise should be prescribed to optimize glucose control remains controversial [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond pharmacological treatments, different lifestyle strategies can attenuate postprandial glycemic excursions. Among these, exercise is widely recognized as a valid tool for improving glycemic control and post-meal glycemic response, not only in patients with diabetes but also in healthy individuals [ 3 , 4 , 5 , 6 ]. Given that various exercise strategies can potentially be used to improve postprandial glycemia, it is important to understand how exercise should be prescribed for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this proof-of-concept study was to see if WI could provide comparable effects as an exercise substitute for those who cannot perform sufficient volumes of exercise. Previous research comparing 30–45 min of post-meal exercise has found similar benefits for post-prandial glucose, however, benefit to fitness and exercise performance needs to be further investigated ( Bellini et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%